CHALLENGES OF STUDYING ISLAMIC JURISPRUDENCE IN THE ERA OF GLOBALIZATION (European Journal of Interdisciplinary Research and Development, 2025)
The study of Islamic jurisprudence (fiqh) in the era of globalization presents a complex array of challenges that demand critical examination. As societies become increasingly interconnected, traditional interpretations of Islamic law face pressures from diverse cultural, social, and legal frameworks. This intersection raises vital questions about the adaptability of Islamic principles to modern legal systems and ethical norms, often leading to tensions between preserved religious tenets and evolving global standards. The proliferation of digital platforms, while facilitating the dissemination of Islamic teachings, also contributes to the misrepresentation and misunderstanding of its core tenets. This paper explores the multifaceted challenges of studying Islamic jurisprudence in a globalized world, focusing on the interplay between traditional and modern interpretations, the impact of colonialism, the influence of Western legal systems, and the role of technology in shaping contemporary legal discourse.